UWI's contribution to Caribbean education: An assessment - Miller, Errol L. (UWI, 1990)
This paper examines the contribution of The University of the West Indies (UWI) to Caribbean education. The basic argument is that UWI has contributed to regional education by virtue of being the regional university, as well as through its actions in supplying manpower needs, guaranteeing standards in teacher education, implementing and managing regional projects, conducting research and engaging in outreach activities. UWI's being and actions are interpreted in the context of the increasing importance of education in several countries, expanding enrollments, improving standards, and persistent colonial patterns. The conclusion is reached that UWI has made no difference where it has merely served the manpower needs of national economies. However, where it has created new stakeholders in Caribbean society, it has acted as a change agent. The institution's greatest contribution is still to come as it helps the region to think through intriguing paradoxes
Keywords: The University of the West Indies